Analysis of YouTube as a source of information for restless leg syndrome - ARIKANOGLU, Adalet; DEMIR, Melike; ALUCLU, Mehmet Ufuk (Arquivos de Neuro-Psiquiatria, 2020)
Background: YouTube is one of the major resources for health related videos around the world. Objective: The aim of this study was to evaluate the quality of information available on YouTube about restless leg syndrome (RLS). Methods: A YouTube search was carried out on https://www.youtube.com for videos pertaining to "restless leg syndrome" by using the keyword "restless leg syndrome". The first 100 relevant videos were included in the study. The videos were accepted as "useful" if they provided scientifically correct information about any aspect of RLS. The videos containing scientifically unproven information are defined as "misleading". The overall quality of all videos was subjectively graded using the global quality scale (GQS), a 5-point Likert scale. Results: The median video length for the included videos was 3.39 (0.11-85) minutes, and the median views were 6,055 (32-2351490). The median GQS of useful videos was 3 (1-5). The median number of likes and the median number of comments of personal experience videos were significantly higher than that of the useful and misleading videos. Videos uploaded by the university hospitals frequently issued pharmacological treatment of the RLS; however, those uploaded by practitioners, individual users, and TV or social media accounts were about the non-pharmacological treatment of the RLS. Conclusions: This study demonstrates that 77% of the videos uploaded on YouTube regarding RLS are in the useful category, whereas only 16 videos were providing misleading information. However, even videos in the useful category do not provide a full and complete description of the RLS.
Keywords: Restless Legs Syndrome; YouTube; Information